THE USE OF PODCAST MEDIA IN LITERAL LISTENING SUBJECT TO SECOND SEMESTER STUDENTS OF ENGLISH TADRIS STUDY PROGRAM 2020/2021 AT IAIN PALU - -, nurhikmah; Ihsan, Muhammad; Afifah, Afifah; Dzakiah, Dzakiah (Datokarama English Education Journal, 2021)
This paper focuses on the use and response of students related to podcast media in literal listening subject to second semester students of the English Tadris Study Program at State Institute for Islamic Studies (IAIN) Palu. The author applies a qualitative research design. The method used in this research is interview and literature study, the results of the study show that the use and response of students regarding podcast media is good, this is evidenced by the results of interviews conducted by researchers with students who are taught using podcast media and lecturers who present material using podcast media.